Drymadusini katydids (Orthoptera: Tettigoniidae; Tettigoniinae): intraspecific variability—morphs or subspecies? - Korsunovskaya, Olga (Zootaxa, 2024)
A new subspecies of Lithoxenus haptapotamicus minutus Korsunovskaya subsp. nov. and new color form of Eulithoxenus mongolicus caeruleum are described. Data concerning the male calling song of L. miramae (Velt.) and the structure of the sound apparatus of Eulithoxenus mongolicus Uv.and L. miramae is provided for the first time.